Ubiquitin D is an independent prognostic marker for survival in stage IIB–IIC colon cancer patients treated with 5‐fluoruracil‐based adjuvant chemotherapy. Issue 4 (April 2015) - Zhao, Senlin; Jiang, Tao; Tang, Huamei; Cui, Feifei; Liu, Chenchen; Guo, Feng; Lu, Huijun; Xue, Yingming; Jiang, Weiliang; Peng, Zhihai; Yan, Dongwang
Abstract: Background: Postoperative 5‐fluoruracil (5‐FU)‐based adjuvant chemotherapy is recommended for stage II colon cancer patients with high conventional risk factors; however, some of these patients still experience tumor recurrence. Identifying novel biomarkers to distinguish the risk of tumor recurrence after surgery is vital for improving their prognoses. We previously showed that ubiquitin D (UBD) can predict the prognosis of colon cancer; however, there are limited data on whether UBD is an independent prognostic factor for stage II patients treated with 5‐FU‐based adjuvant chemotherapy. Methods: Quantitative real‐time PCR and Western blot analyses were used to examine UBD expression in randomly selected stage II patients' tumor tissues. UBD expression and p65 distribution were assessed using immunohistochemistry in paraffin‐embedded specimens from the 101 tumor recurrence patients and 178 nonrelapse patients who received postoperative 5‐FU‐based adjuvant chemotherapy. Results: UBD expression, both at transcriptional and posttranscriptional levels, was higher in relapse tumors ( P < 0.001). Immunohistochemistry staining of UBD and p65 showed significant differences between the two groups ( P < 0.001). Patients with tumor tissues that UBD‐positive expression alone or in combination with p65 nuclei translocation recurred early had a significantly shorter survival time ( P < 0.001), especially in stage IIB‐IIC patients. UBD‐positive expression accompanied with p65 nuclei translocation was a significant independent predictive high risk factor for overall survival (HR 8.76; 95% CI, 5.35–14.27; P = 0.004) and disease‐free survival (HR 5.70; 95% CI, 1.43–11.55; P = 0.016). Conclusion: UBD may help to identify recurrent risk in stage IIB‐IIC colon cancer patients and further predict which patients benefit from postoperative 5‐FU‐based adjuvant chemotherapy.